Alive attenuated Salmonella as a cargo shuttle for smart carrying of gold nanoparticles to tumour hypoxic regions. (16th March 2019) - Kefayat, Amirhosein; Ghahremani, Fatemeh; Motaghi, Hasan; Rostami, Soodabeh; Mehrgardi, Masoud A.
Abstract: In the present study, alive attenuated Salmonella typhi Ty21a was introduced as a vehicle for smart delivery of gold nanoparticles to the tumours' hypoxic regions. At the first step, the uptakes of gold nanoparticles with seven different decorations by S . typhi Ty21a was investigated using flow cytometry and inductively coupled plasma optical emission spectroscopy. The analyses demonstrated that folic acid functionalised gold nanoparticles (FA-GNPs) are the best candidates for producing the Golden Bacteria (GB). Subsequently, the GB and FA-GNPs efficacies for tumour targeting were investigated after intravenous injection to CT-26 tumour-bearing mice. The GB exhibited more GNPs delivery to the tumour in comparison with FA-GNPs. Moreover, GB injection causes more delivery of GNPs to the tumours' central regions in comparison with tumours' periphery. This trend is completely in reverse for FA-GNPs injected group. The ratios of peripheral to central regions' gold concentration of the tumours were 1.95 ± 0.13 and 0.61 ± 0.10 for FA-GNPs and GB groups, respectively. This observation demonstrates higher accumulation of gold nanoparticles in the centre of the tumour due to their active delivery by the S . typhi Ty21a to the deeps of tumours.